Finnish and Estonian teachers’ views on the nature of intelligence - Ronkainen, Rina; Kuusisto, Elina; Eisenschmidt, Eve; Tirri, Kirsi (Frontiers in Education, 2022)
The purpose of this study was to investigate Finnish (n=226) and Estonian (n=347) teachers’ views on the nature of intelligence. The study utilized a survey that included a qualitative, open-ended question about teachers’ definition of intelligence and the quantitative inventory Implicit Theories of Intelligence (ITI). We then employed a convergent mixed-method design to understand teachers’ views on the nature of intelligence. These views were divided into four main categories: the multidimensional nature of intelligence, manifestational nature of intelligence, developmental nature of intelligence, and creative nature of intelligence. Teachers from both countries highlighted cognitive features, such as memory, information processing, and problem-solving skills, as a part of the multidimensional nature of intelligence. In addition, teachers viewed intelligence as developmental when measured with the ITI inventory, indicating that intelligence is considered incremental. Lastly, when triangulating the qualitative and quantitative data of teachers’ views on the nature of intelligence, only one statistically significant difference was found. Teachers with an entity view of intelligence also mentioned entity features in their own descriptions. The results showed that teachers views’ on the nature of intelligence are rather broad; however, in future studies, teacher interviews and classroom observation might provide even more profound understanding of teachers’ views on this topic.